Modelling of broadband noise radiated by an airfoil-application to an axial fan. (5th July 2007) - Fedala, D.; Kouidri, S.; Bakir, F.; Rey, R.
In this paper, a modelling of the broadband noise radiated by an axial subsonic fan is presented and validated. It is an extension of Amiet's model predicting the broadband noise generated by an isolated airfoil. Two sources are analysed, incident turbulence interaction noise and trailing edge noise. It shows the dominance of the leading edge noise. The broadband noise directivity for axial fans presents a main radiation lobe along the fan axis for both mechanisms. It was observed that the leading edge acoustic spectra feature is very sensitive to the turbulence length scale of the incident flow.